Early tumor shrinkage indicates a favorable response to bevacizumab-based first-line chemotherapy for metastatic colorectal cancer. Issue 10 (November 2017) - Ito, Mamoru; Kusaba, Hitoshi; Mukaide, Satomi; Kishimoto, Junji; Shimokawa, Hozumi; Tamura, Shingo; Makiyama, Akitaka; Hirano, Gen; Oda, Hisanobu; Shirakawa, Tsuyoshi; Komoda, Masato; Uchino, Keita; et al.
Abstract : A close correlation between early tumor shrinkage (ETS) and overall survival (OS) has been shown in antiepidermal growth factor receptor antibody-based chemotherapies for metastatic colorectal cancer (mCRC), but the clinical impact of ETS in bevacizumab-based chemotherapy has not been adequately clarified. Clinical data of mCRC patients who started initial chemotherapy without antiepidermal growth factor receptor antibody from 2005 to 2010 were retrospectively evaluated. The relative change in tumor size after 8 weeks of chemotherapy expected from the first image assessment [estimated ETS (EETS)] and the relative change in the tumor size at the nadir compared with the baseline [depth of response (DPR)] were examined. Seventy-three patients were enrolled and 61 patients were evaluable for survival by simple regression analysis. Bevacizumab-based chemotherapies were administered to 40 (66%) patients. The median EETS, DPR, progression-free survival, and OS were 16.1%, 27.2%, 8.0 months, and 19.5 months, respectively. Progression-free survival showed a positive correlation with OS ( R 2 =0.429), whereas EETS and DPR were less correlated with OS ( R 2 =0.0682, 0.186). EETS was well correlated with DPR ( R 2 =0.659). Patients with EETS greater than 16.12% were predicted to achieve tumor shrinkage of more than 30% at the maximum response. EETS in bevacizumab-treated mCRC showed a close correlation with DPR, which suggested that EETS might be useful, indicating a favorable response in treatment with bevacizumab-based chemotherapy.